2015
DOI: 10.1016/j.afju.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

A review of transrectal ultrasound guided prostate biopsies: Is there still a role for finger guided prostate biopsies?

Abstract: Objective: We compared our institution's initial experience with transrectal ultrasound-guided (TRUS) prostate biopsies in a single arm prospective study to a historical cohort of finger guided (FG) biopsies. The primary outcome measure was prostate cancer detection. We documented our findings on TRUS including the findings of peripheral calcifications, hypoechoic lesions and capsular distortion and evaluated whether these had any significance in prostate cancer detection. Patients and methods: All patients pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…[36] It is interesting to note that a study in Cape Town, SA, found that TRUSguided prostate biopsy only outperformed finger-guided biopsies in terms of cancer detection when the PSA level was <20 ng/mL, which only became statistically significant when the PSA level was <10 ng/ mL, irrespective of the DRE findings. [37] The authors noted that, while far from the gold standard, finger-guided prostate biopsies remain a suitable alternative in resource-limited settings, especially when the prostate is clinically abnormal.…”
Section: Africamentioning
confidence: 99%
“…[36] It is interesting to note that a study in Cape Town, SA, found that TRUSguided prostate biopsy only outperformed finger-guided biopsies in terms of cancer detection when the PSA level was <20 ng/mL, which only became statistically significant when the PSA level was <10 ng/ mL, irrespective of the DRE findings. [37] The authors noted that, while far from the gold standard, finger-guided prostate biopsies remain a suitable alternative in resource-limited settings, especially when the prostate is clinically abnormal.…”
Section: Africamentioning
confidence: 99%
“…The 12 regions of the prostate were covered by the systematic biopsy, which was carried out by putting the needle following an in-house scheme (medial and lateral apex, medial and lateral mid prostate, and medial It is interesting to note that a newer study found that patients with suspicious DRE and PSA above 10 ng/ml do not have a statistically significant difference in cancer detection rates, with 45.6 and 48.6% for finger guidance and TRUS, respectively (P = 0.27) [6]. Fingerguided biopsies are still employed to diagnose PCa in some low-resource units when TRUS is unavailable and are indicated in the case of locally advanced disease or palpable prostatic nodules.…”
Section: Biopsy Protocolsmentioning
confidence: 99%
“…Their results demonstrated finding cancer in 53% of the time in patients with previously negative finger-guided biopsies ( n = 43) and confirming previously diagnosed cancer in 94% of subjects. 38 , 39 In the same year, Hodge et al published findings on systematic sampling. 39 41 In what would become known as the sextant technique, biopsy cores were taken from six regions of the prostate: apex, middle, and base of each lobe parasagitally in addition to any hypoechoic lesions identified on ultrasound.…”
Section: Early Efforts To Transperineally Biopsy the Prostatementioning
confidence: 99%